Pengembangan Media Pembelajaran Matematika Berupa Kotak Pop-Up untuk Anak Autisme - Aprilia, Eka; Supriadi, Nanang (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to develop learning media in the form of pop-up boxes that are effective and in accordance with the criteria for autistic children. This type of research used in this research is research and development (Research and Development). In this study using ADDIE research methods, namely Analysis, Design, Development, Implementation, Evaluation. Data collection techniques used were test and non-test instruments, data analysis techniques to calculate the validity of the media, students' responses and the effectiveness of instructional media. Validation in this research is based on the validation of media experts and students to determine the response and effectiveness of the resulting media. The results of validation by media experts are 2.67 with the criteria of